Psychotherapy transcription standards [data] - Dönnhoff, Ivo; Langhoff, Bea-Marie; Xiong, David; Bergner, Thilo; Montan, Inka; Spranz-Fogasy, Thomas; Deppermann, Arnulf; Friederich, Hans-Christoph; Nikendei, Christoph (Universität, 2026)
The datasets contains the newly developed psycholotheraupeutically informed transcription rules we developed within our study. These transcription rules can be used to transcribe psychotherapeutic settings or can be implemented into AI. We further provide the RMarkdown files for our four case studies. Due to restrictions by the ethical board commitee, the videografed psychotherapy sessions and questionnaires can not be shared. Thus, we provide the RMarkdown files which both contain our code and the corresponding results.